Socio-economic status of fishers of the old Brahmaputra river in Mymensingh sadar upazila, Bangladesh - Saberin, Imam Sayeda; Reza, Md Shaheed; Mansur, Md Abul; Kamal, Md (Research in Agriculture Livestock and Fisheries, 2017)
A survey was conducted to assess the socio-economic status of the fishers of the old Brahmaputra River in Mymensingh Sadar Upazila from April 2011 to March 2012. Data were collected from randomly selected 30 traditional fishermen of Kagdahor, Shambhuganj, Kawatkhali, BAU Campus, Shesmor, Sutiakhali, Char Kalibari, Char Ishwardia and Char Nilakshmia using a well-structured questionnaire. The research revealed that besides fishing, the fishers occasionally undertook a variety of non-fishery related activities. The average annual income ranged from 25,000-84,000 BDT which significantly depends on fishing effort, season of the year and market price of fish. Majority of them belonged to age range 15-30 years (59.25%). Almost 63% of the fishermen were illiterate and cannot write their names, while only 14.81% had received education up to primary level. It was also revealed that family size of 60% of the fishermen were medium consisting of 5-7 members while only 10% had small family size of 2-4 members. Despite their low income and large family sizes, 80% of the fishermen were living in semi-constructed houses. Sometimes for coping with adverse situation many of them took loans from different national and local NGOs like BRAC, ASSA. A declining trend of fish resources in the river and lack of working capital were identified as the major constrains for the fishers of the Old Brahmaputra River. Res. Agric. Livest. Fish.4(3): 229-235, December 2017